Effects Of The Cyclic Prefix In Siso And Miso Wimax Systems (International Journal of Engineering and Computer Science, 2012)
The cyclic prefix (CP) is actually a copy of the last portion of the data symbol appended to the front of the symbol during the guard interval (GI). By adding a CP, the channel can be made to behave as if the transmitted waveforms were from time minus infinite, and thus ensure Orthogonality, which essentially prevents one subcarrier from interfering with another (called intercarrier interference (ICI)).This paper demonstrates the effects of the CP on the single input/single output (SISO) and multi input/single output (MISO) WiMAX systems. In this work, the effect of different values of CP is shown in term of bit error rate (BER) and signal to noise ratio (SNR). This work shows also the impact of the adaptive modulation and coding (AMC) on data transmission rate with different values of the CP. The contribution of this work is twofold; first, it shows the best value of the BER for different values of the CP using AMC. Second, shows the effect fading for different values of the CP.